The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.33429/cjas.10119.1/6
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price and Exchange Rate Nexus in Nigeria: Are there Asymmetries

Abstract: This paper examines the dynamics in the relationship between oil price and exchange rate in Nigeria by utilizing monthly data spanning January 1986 to June 2018. It specifically determines asymmetries in the relationship between oil price and exchange rate and the effect of oil price shocks on exchange rate. Threshold Autoregressive (TAR), Momentum Threshold autoregressive (MTAR) and Structural Vector Autoregressive (SVAR) models were employed for the analysis. Findings of TAR and MTAR models confirm the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…Several studies have been conducted in Nigeria on the nexus that exist between stable exchange rate and oil price volatilities. Notable amongst these studies is Mohammed et al (2019) and Abubakar (2019). Their conclusions revealed a positive relationship between exchange rate and crude oil price in Nigeria.…”
Section: Introductionmentioning
confidence: 92%
“…Several studies have been conducted in Nigeria on the nexus that exist between stable exchange rate and oil price volatilities. Notable amongst these studies is Mohammed et al (2019) and Abubakar (2019). Their conclusions revealed a positive relationship between exchange rate and crude oil price in Nigeria.…”
Section: Introductionmentioning
confidence: 92%
“…As a corollary, the studies on oil‐importing economies that found asymmetric relationships include Churchill et al, 2019; Kumar, 2019; Khraief et al, 2020; Bangura et al, 2021. By contrast, however, the studies of Abubakar (2019); and Ben‐Dhiab et al (2021) found no evidence for the existence of asymmetric relationships. Empirical studies that included a panel of oil‐importing and oil‐exporting countries and obtained asymmetric relationships include the studies of Kisswani et al, 2018; Salisu et al, 2020; Kisswani & Elian, 2021, while the studies of Saidu et al (2021) and Huang et al (2020) could not find evidence for asymmetric relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Salisu et al (2020) adopt a quasi‐GLS estimator, Abubakirova et al (2021) used the asymmetric non‐causality test of Hatemi‐J and Roca (2014) test while Nouira et al (2018) utilised the non‐causality test of Hatemi‐J (2012). The study of Huang et al (2020) employed the use of pairwise VAR technique while Olayeni et al (2020) and Abubakar (2019) adopt various threshold models.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies, shock on crude oil prices is not inflationary. Abubakar (2019) adopt TAR and MTAR to examine the asymmetry of oil price and exchange rate in Nigeria. The study data range from 1986M01 to 2018M06.…”
Section: Empirical Literaturementioning
confidence: 99%